The Effect Of Work Stress and Emotional Intelligence On Job Satisfaction And Its Impact On The Performance Of Nurses At Palembang Bari Regional General Hospital - Desiana; Djatmiko Noviantoro; Nashir; Sari Sakarina (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
A hospital is an integral part of a health and social organisation with various functions, particularly in providing services, preventing, and treating diseases in the community. Nurses, as